Water, starch, and nuclear behavior in ray parenchyma during heartwood formation of Catalpa bungei ‘Jinsi’ - Pingping Guo; Xiping Zhao; Zifei Yang; Yingxin Wang; Hongying Li; Lepei Zhang (Heliyon, 2024)
Catalpa bungei ‘Jinsi’, a cultivar of C. bungei C. A. Mey., is valued for its heartwood with good overall mechanical properties, naturally durable and golden-yellow color. Little is known about heartwood formation in C. bungei ‘Jinsi’ trees. The behavior of starch, water, and nuclei was studied in the xylem tissue of C. bungei ‘Jinsi’ concerning aging in ray parenchyma cells. Blocks containing heartwood, golden zone, transition zone, and sapwood were collected from the stems of six C. bungei ‘Jinsi’ trees. The moisture content of the blocks was measured by oven drying. Changes in starch and nuclei in ray parenchyma were investigated in radial profiles from sapwood to heartwood blocks using microscopy and various staining techniques. The nuclear size and starch content gradually decreased to heartwood. While the horizontal distribution of moisture content of C. bungei ‘Jinsi’ was very varied, with the heartwood and golden zone being lower than sapwood but slightly higher than the transition zone. Starch grains were rare, but nuclei were still present in some ray parenchyma cells in the heartwood and golden zone. The nuclei showed irregular shape and elongation before disintegration. These results suggest that the most apparent change occurs in the transition zone, the critical location involved in forming C. bungei ‘Jinsi’ heartwood. Water and starch appear to be actively engaged in heartwood formation. The loss of function of ray parenchyma cells results from heartwood formation.